Rancang Bangun Sistem Keamanan Sepeda Motor Dengan Fingerprint Berbasis Telephone - Suhari janto; Affan Bachri (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2018)
This research uses fingerprint as the security system. This tool checks if there is a match between the data obtained from the verification process and data stored on the file, if it matches then the motorcycle engine will light up. If there is stranger tries to put his finger into the fingerprint tool installed in the motorcycle, it will be rejected and the GSM SIM 900 module will inform the owner via phone that the motorcycle is in unsafe condition